Bibliometric Analysis: The Use of Quizizz Paper Mode Application to Increase Student Learning Motivation - Kamaliah, Nor; Mansur, Hamsi; Rini, Sulistyo (STKIP Al Islam Tunas Bangsa dan HEPI, 2025)
Technological advancements in education have encouraged innovation in learning methods, including Quizizz paper mode as an interactive assessment tool. This study aims to determine the effectiveness of the Quizizz paper mode application in increasing student learning motivation and to examine the development of Quizizz paper mode over the last 5 years (2020–2024). The type of research used is descriptive quantitative with bibliometric analysis using VOSviewer software. The results and discussion show that Quizizz paper mode positively influences student learning motivation through a fun, effective, and innovative interactive method that supports the learning process. The development of Quizizz paper mode in the last five years has seen a significant increase in 2023 and 2024, reflecting strong interest from researchers in the topic of using Quizizz paper mode to boost learning motivation. It is expected that this research can serve as a reference for future studies in exploring the role of interactive, game-based technology like Quizizz paper mode and assist in designing its effective use in educational settings.